2015
DOI: 10.1002/mnfr.201500441
|View full text |Cite
|
Sign up to set email alerts
|

Glabridin, an isoflavan from licorice root, upregulates paraoxonase 2 expression under hyperglycemia and protects it from oxidation

Abstract: Such results indicate that glabridin preserves the anti-atherogenic abilities of PON2 by maintaining its levels, in vivo. The glabridin-PON2 interaction may be the mechanism by which glabridin protects PON2 from oxidation, thus contributing to the protection of PON2 activity in hyperglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 55 publications
(90 reference statements)
1
19
0
Order By: Relevance
“…PON2 mRNA and protein downregulation under hyperglycemic conditions is supported by previous studies on macrophages and monocytes [37,49]. Moreover, a lower PON2 expression has been observed in liver and heart of hyperglycemic animal models [37,49].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…PON2 mRNA and protein downregulation under hyperglycemic conditions is supported by previous studies on macrophages and monocytes [37,49]. Moreover, a lower PON2 expression has been observed in liver and heart of hyperglycemic animal models [37,49].…”
Section: Discussionsupporting
confidence: 70%
“…In fact, a decrease of PON2 has been observed in Caco-2 cells oxidized by iron-ascorbate [27] or by treatment with H 2 O 2 [48]. PON2 mRNA and protein downregulation under hyperglycemic conditions is supported by previous studies on macrophages and monocytes [37,49]. Moreover, a lower PON2 expression has been observed in liver and heart of hyperglycemic animal models [37,49].…”
Section: Discussionmentioning
confidence: 70%
“…Total RNA was isolated from THP-1 cells using the RNeasy Mini Kit including RNase-free DNase set (Qiagen, Hilden, Germany). Using the Transcriptor First-Strand cDNA Synthesis Kit (Roche Diagnostics, Mannheim, Germany), cDNA was synthesized from 2 μg of total RNA using oligo-dT (12)(13)(14)(15)(16)(17)(18) and 5 units of avian myeloblastosis virus reverse transcriptase at 50 C for 60 min, followed by heating to 85 C for 5 min. For further PCR amplification, an aliquot (1:10) of the realtime (RT) product was adjusted to contain 0.1 μg of each primer, and additional buffer was added to a final volume of 20 μL.…”
Section: Real-time Polymerase Chain Reaction Assaymentioning
confidence: 99%
“…Yang et al found that liquorice flavonoid can effectively enhance insulin secretion in high‐fat diet administered mice through JNK1‐dependent protein tyrosine phosphatase 1B (PTP1B) signaling. Glabridin, an isoflavan from liquorice root, has also been found in upregulating paraoxonase 2 expression and decreasing iNOS activity in saturated fatty acid‐fed diabetic mice . Besides, the natural compound of amorfrutins, extracted from Glycyrrhiza foetida , has showed powerful antidiabetic capacity by dramatically reducing insulin resistance, inflammatory phenomena, and without side effects such as hepatotoxicity by activating peroxisome proliferator‐activated receptor γ (PPARγ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation